Assistance dogs provide a useful behavioral model to enrich communicative skills of assistance robots - Gácsi, Márta; Szakadát, Sára; Miklósi, Ádám (Frontiers in Psychology, 2013)
These studies are part of a project aiming to reveal relevant aspects of human-dog interactions, which could serve as a model to design successful human-robot interactions. Presently there are no successfully commercialised assistance robots, however, assistance dogs work efficiently as partners for persons with disabilities. In Study 1, we analysed the cooperation of 32 assistance dog-owner dyads performing a carrying task. We revealed typical behaviour sequences and also differences depending on the dyads’ experiences and on whether the owner was a wheelchair user. In Study 2, we investigated dogs’ responses to unforeseen difficulties during a retrieving task in two contexts. Dogs displayed specific communicative and displacement behaviours, and a strong commitment to execute the insoluble task. Questionnaire data from Study 3 confirmed that these behaviours could successfully attenuate owners’ disappointment. Although owners anticipated the technical competence of future assistance robots to be moderate/high, they could not imagine robots as emotional companions, which negatively affected their acceptance ratings of future robotic assistants. We propose that assistance dogs’ cooperative behaviours and problem solving strategies should inspire the development of the relevant functions and social behaviours of assistance robots with limited manual and verbal skills.